Fossils reveal a high diversity of the staghorn coral genera Acropora and Isopora (Scleractinia: Acroporidae) in the Neogene of Indonesia. (December 2015) - Santodomingo, Nadiezhda; Wallace, Carden C.; Johnson, Kenneth G.
Abstract : Although Acropora is the most diverse and abundant coral genus on modern Indo‐Pacific reefs, there is only limited understanding of its evolutionary history in the region. To help fill this gap, we consider the fossil record of Acropora and its sister clade Isopora, through examination of new extensive collections of well‐preserved specimens from East Kalimantan, Indonesia, of Miocene age, historical museum collections, and literature records throughout the Indo‐Pacific. We examined a total of 226 lots including 4720 specimens, from which 33 species were described, 31 Acropora and two Isopora . Descriptions are based on qualitative morphological characters and 17 quantative characters. We report the first appearance in the fossil record of the nasuta, elegans and loripes species groups, in the Miocene. We describe seven new species: six Acropora ( A . laurae, A . elenae, A . emanuelae, A . darrellae, A . hasibuani and A . renemai ) and one Isopora ( I . matahari ) which, at 17.9 Ma, is the earliest known occurrence of Isopora . Moreover, we extend the occurrence of the species A. lavandulina and A. bartonensis, previously reported from the Eocene and Oligo‐Miocene of Europe, into the Oligocene and Miocene of the Indo‐Pacific, respectively. We confirm that 31 species within nine Acropora species groups were already present in the Indo‐Pacific in the Miocene, with a maximum age of 18–20 Ma, supporting the large body of evidence indicating an early origin for most Acropora lineages and the evolutionary persistence of species groups throughout the Cenozoic. Based on our new data, 23 extant species have their earliest occurrence during the Neogene, including 12 that were already present in the Early Miocene. Four principal palaeoenvironments were interpreted from our samples of East Kalimantan, mostly associated with shallow turbid habitats. The arrangement sequence of radial corallites with respect to the axial corallite is proposed as a new morphological character to distinguish species and/or species groups. We expect that the full set of morphological features that we present in this study will allow the integration of the fossil record into comprehensive phylogenetic analyses that give more insights into the complex evolutionary history of Acropora . © 2015 The Linnean Society of London